How important is social support in adolescence? Social support as a predictor of adolescent mental health in Serbia - Trbojević, Jovana; Balać, Kristina (Psihološka istraživanja, 2026)
The aim of this study is to examine the predictive role of perceived social support in adolescent mental health. The sample consisted of 217 secondary school students from Kragujevac (Republic of Serbia), aged 16 to 18. Perceived social support from family, friends and significant others was assessed, along with the levels of depression, anxiety, stress and life satisfaction as indicators of mental health. Adolescents in Serbia reported a high level of perceived social support from family, friends and significant others, with adolescent girls scoring significantly higher on the overall perceived social support, as well as on the support from friends and significant others. No gender differences were found in the perceived family support. The results also showed that adolescent girls reported significantly higher levels of depression, anxiety and stress compared to boys. Regression analyses indicated that social support (from family, friends and significant others) significantly predicted all mental health indicators, explaining between 7.9% and 19% of variance, with family support emerging as the most significant individual predictor. These findings highlight the importance of the family system as a key protective factor for adolescent mental health and underscore the need to design preventive and educational programmes aimed at strengthening family and peer support networks in order to promote adolescents’ psychological well-being.
Keywords: social support; satisfaction with life; depression; anxiety; stress; adolescence